Explorer la perception d’enfants de maternelle de leur participation lors de la lecture d’histoire en classe et de leur intérêt à la lecture : une étude pilote - McMahon-Morin, Paméla (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
This pilot study explores the perception of kindergarten children regarding their participation during storybook reading in class and their interest in reading, as a proof of concept of using this source of data in extended research. Six children participated in an online, semi-structured individual interview, which was analyzed qualitatively with a thematic analysis (Braun & Clarke, 2013). Results suggest that the children participate when the teacher asks a question to the class, rather than through their own initiative. The participants’ testimonials reveal a certain tension between the children’s participation and the class management provided by their teacher. Results suggest as well that the children’s interest in reading does not necessarily translate into frequent autonomous reading habits in class, nor does it lead to being perceived as a reader. One child had a teacher who received professional development on interactive book reading, and the use of this approach was evident in this child’s interview. The results justify further research on children’s participation during storybook reading and their interest in reading using the perception of children, even as young as kindergarten age, as a source of data. The latter could also be useful for documenting the impact of interventions on reading practices. Verbatims from this study could be incorporated into professional development for teachers.